HUBUNGAN DUKUNGAN SOSIAL DAN GANGGUAN JIWA RINGAN (COMMON MENTAL DISORDERS=CMDs) PADA IBU HAMIL DENGAN KEJADIAN PREEKLAMSIA/EKLAMSIA DI KABUPATEN SUKOHARJO JANUARI 2010-DESEMBER 2011 - , Yudhi Wibowo, Prof. dr. H. M. Hakimi, Sp.OG (K), Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: In 2010, the highest direct cause of maternal mortality was preeclampsia/ eclampsia (PE/E) (47.62%). Social support influenced the mental health in pregnant women according to different family structure. The distress during pregnancy was likely to lead to PE/E. In Sukoharjo, there were increased psychosis cases from 1387 (2008) to 2445 (projected in 2010). The objective was to analyze the association of social support and common mental disorders (CMDs) in pregnant women with PE/E. Methods: This study was a matched case-control study. Cases were pregnant women who have been diagnosed with PE/E by a hospital specialist. Controls were pregnant women with normal pregnancies or not diagnosed as PE/E by health workers. Instruments: social demographic questionnaire, SSQ-6 and SRQ20. Analysis using Chi Square, McNemar, stratified analysis, and conditional logistic regression multiple. Results: Respondents were 286 people, 56.99% live in nuclear family, 45.10% had low social support, and 27.27% had CMDs (+). Low social support was not directly associated to PE/E. Compared with high social support, those with low social support had a 26 fold increased risk of CMDs (+) (p<0.01, OR=26.4, 95% CI: 10.67 to 77.20). Several variables significantly associated with PE/E were CMDs (+) (p<0.01, OR=6.11, 95% CI: 2.99 to 14.07), low family income (p<0.01, OR=2 , 93, 95% CI: 1.56 to 5.82), history of chronic hypertension (+) (p<0.01, OR=7.67, 95% CI: 2.32 to 39.89), history of PE/E (+) (p<0.01), and history of hereditary of PE/E (+) (p=0.01, OR=6, 95% CI: 1.34 to 55.20). Conclusion: Low social support was not directly associated to PE/E but it was associated to CMDs (+). CMDs (+), low family income, history of chronic HT (+), history of PE/E (+), and history of hereditary of PE/E (+) were associated to PE/E. There is need for an integrated service between the MCH program, noncommunicable diseases prevention program, and mental health, as well as social support from family. Future study should specify the methodology and the improvement of social support in the emotional and instrumental support as well as the quality of the relationship.